2021
DOI: 10.1103/physrevd.103.014511
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark momentum diffusion from the lattice using gradient flow

Abstract: We apply the gradient flow on a color-electric two-point function that encodes the heavy quark momentum diffusion coefficient. The simulations are done on fine isotropic lattices in the quenched approximation at 1.5 Tc. The continuum extrapolation is performed at fixed flow time followed by a second extrapolation to zero flow time. Perturbative calculations of this correlation function under Wilson flow are used to enhance the extrapolations of the non-perturbative lattice correlator. The final estimate for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 51 publications
3
57
2
Order By: Relevance
“…It is found that a relatively strong increase of 2Ο€ T D s (T ) from crossover temperature T c toward high temperature. Meanwhile, the v 2 data prefers a small value of 2Ο€ T D s near T c , 2Ο€ T D s (T c ) 3βˆ’6 4 , which is close to the lattice QCD calculations [64][65][66][67][68]. Charm Fig.…”
Section: Energy and Temperature Dependence Of The Transport Coefficientssupporting
confidence: 82%
See 1 more Smart Citation
“…It is found that a relatively strong increase of 2Ο€ T D s (T ) from crossover temperature T c toward high temperature. Meanwhile, the v 2 data prefers a small value of 2Ο€ T D s near T c , 2Ο€ T D s (T c ) 3βˆ’6 4 , which is close to the lattice QCD calculations [64][65][66][67][68]. Charm Fig.…”
Section: Energy and Temperature Dependence Of The Transport Coefficientssupporting
confidence: 82%
“…LGR [40], LIDO [60], Catania [61] and CUJET3 5 [18,20,21], show a similar trend but with much weaker temperature dependence. LGR (dotted blue curve [40], LIDO (dashed black curve [60]), Catania (dot-dashed green curve [61]), CUJET3 (shadowed red band [18,20,21]) and lattice QCD calculations (black circle [64], blue triangle [65], pink square [66], red inverted triangle [67] and green plus [68]). The result for D-meson (long dashed pink curve [69]) in the hadronic phase is shown for comparison…”
Section: Energy and Temperature Dependence Of The Transport Coefficientsmentioning
confidence: 99%
“…Given that colour interactions are strong in QCD, their effects should be investigated up to the non-perturbative level. For colour-electric forces, large-scale lattice simulations have indeed been carried out in recent years [8][9][10][11][12][13], whereas for the colour-magnetic corrections, the challenge lies ahead of us. In preparation for this task, the goal of the current study is to clarify the renormalization of the colour-magnetic part of eq.…”
Section: Introductionmentioning
confidence: 99%
“…The chromoelectric correlator is very noisy and to reduce the noise the multi-level algorithm has been used in the above studies. Recently, it has been suggested to use the gradient flow as an alternative noise reduction method and this approach turned out to be successful in calculating the heavy quark diffusion coefficient at 1.5𝑇 𝑐 [12]. Furthermore, in Ref.…”
Section: Introductionmentioning
confidence: 99%